QSAR and docking studies of α,β-unsaturated carbonyl compounds against human breast adenocarcinoma cell line MCF-7 - Almahdi, Maysoon Mohammed; Saeed, Ahmed Elsadig Mohamed; Metwally, Nadia Hanafy (European Journal of Chemistry, 2018)
A quantitative structure-activity relationships (QSAR) studies were carried out by correlating activity against human breast adenocarcinoma cell line MCF-7 of series of α,β-unsaturated carbonyl compounds with their physicochemical descriptors using multiple linear regression method. The predictability of the QSAR model was estimated using internal and external predictivity methods. The best QSAR model was selected, having the squared correlation coefficient r2 = 0.84684, correlation coefficient r = 0.9202, standard deviation s = 0.38484, and cross-validated squared correlation coefficient Q2 = 0.7621. Model obtained was used to predicted the activity against breast cancer for a set of designed α,β-unsaturated carbonyl compounds (A1-A16). Docking studies was performed for A1-A16 compounds to evaluated their inhibition on c-Met kinase, which has been overexpressed in a number of cancers.